On the Interaction Between SMARCAL1 and BRG1 - Bisht, Deepa; Patne, Ketki; Rakesh, Radhakrishnan; Muthuswami, Rohini (Frontiers in Cell and Developmental Biology, 2022)
SMARCAL1 and BRG1, both classified as ATP-dependent chromatin remodeling proteins, play a role in double-strand break DNA damage response pathways. Mutations in SMARCAL1 cause Schimke Immuno-osseous dysplasia (SIOD) while mutations in BRG1 are associated with Coffin-Siris Syndrome (CSS4). In HeLa cells, SMARCAL1 and BRG1 co-regulate the expression of ATM, ATR, and RNAi genes on doxorubicin-induced DNA damage. Both the proteins are found to be simultaneously present on the promoter of these genes. Based on these results we hypothesized that SMARCAL1 and BRG1 interact with each other forming a complex. In this paper, we validate our hypothesis and show that SMARCAL1 and BRG1 do indeed interact with each other both in the absence and presence of doxorubicin. The formation of these complexes is dependent on the ATPase activity of both SMARCAL1 and BRG1. Using deletion constructs, we show that the HARP domains of SMARCAL1 mediate interaction with BRG1 while multiple domains of BRG1 are probably important for binding to SMARCAL1. We also show that SIOD-associated mutants fail to form a complex with BRG1. Similarly, CSS4-associated mutants of BRG1 fail to interact with SMARCAL1, thus, possibly contributing to the failure of the DNA damage response pathway and pathophysiology associated with SIOD and CSS4.